2009
DOI: 10.3399/bjgp09x395102
|View full text |Cite
|
Sign up to set email alerts
|

Web-based learning strategies in combination with published guidelines to change practice of primary care professionals

Abstract: Published clinical guidelines need to be combined with effective educational interventions to produce change in practice. Problem-based learning (PBL) groups are effective; however, research studies have not looked at change in practice following PBL that is independent of group interaction. AimTo determine whether clinical guidelines combined with modified PBL e-learning modules, in which dialogue between learners is replaced by interaction with a computer, could increase knowledge, result in changes in pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…Other authors have also been very optimistic about the use of new technology for CME activities [63,64]. A study by Robson demonstrated an effect of online modules alone on the performance of 45 GPs similar to the findings of Fordis and colleagues [2,10]. Interestingly, both found higher adherence to the recommendations without a gain in knowledge, but Robson asked his participants retrospectively, so there is a high risk of social desirability [2].…”
Section: Discussionmentioning
confidence: 79%
“…Other authors have also been very optimistic about the use of new technology for CME activities [63,64]. A study by Robson demonstrated an effect of online modules alone on the performance of 45 GPs similar to the findings of Fordis and colleagues [2,10]. Interestingly, both found higher adherence to the recommendations without a gain in knowledge, but Robson asked his participants retrospectively, so there is a high risk of social desirability [2].…”
Section: Discussionmentioning
confidence: 79%
“…Simple Educational Tools and Practice Change compared to electronic formats (Turner et al 2006;Kerfoot 2008). One study does report physician acceptance of and some self-reported changes in practice following online problem-based learning modules based on clinical care guidelines (Robson 2009). However, there was little documented change in knowledge and participants volunteered.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence-based educational guidelines recommend this mixed approach [7]. The combination of guidelines and problem-based e-learning plus interaction with the computer increases knowledge and results in change in practice [8]. Schneider et al stated that students using the learning and teaching platform CASUS ® for preparing lectures of VPs lead to improved outcomes [9].…”
Section: Students' Perspectivementioning
confidence: 98%